2012
DOI: 10.1111/j.1440-1746.2012.07098.x
|View full text |Cite
|
Sign up to set email alerts
|

Emu Oil: A novel therapeutic for disorders of the gastrointestinal tract?

Abstract: Gastrointestinal diseases characterized by inflammation, including the inflammatory bowel diseases, chemotherapy-induced mucositis and non-steroidal anti-inflammatory druginduced enteropathy, currently have variably effective treatment options, highlighting the need for novel therapeutic approaches. Recently, naturally-sourced agents including prebiotics, probiotics, plant-extracts and marine-derived oils known to possess antiinflammatory and anti-oxidant properties have been investigated in vitro and in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Recently, a somewhat disparate group of naturallysourced agents have demonstrated improvements in mucositis symptomatology in the experimental setting. These include a whey-derived growth factor extract (9), plant extracts such as grape seed extract (10,11) and Iberogast (12), animal-sourced oils such as emu oil (13)(14)(15)(16) and Lyprinol (17) and certain probiotics (18). However, despite the effectiveness of these compounds, the need to pursue alternative treatment modalities still remains.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, a somewhat disparate group of naturallysourced agents have demonstrated improvements in mucositis symptomatology in the experimental setting. These include a whey-derived growth factor extract (9), plant extracts such as grape seed extract (10,11) and Iberogast (12), animal-sourced oils such as emu oil (13)(14)(15)(16) and Lyprinol (17) and certain probiotics (18). However, despite the effectiveness of these compounds, the need to pursue alternative treatment modalities still remains.…”
Section: Introductionmentioning
confidence: 97%
“…2001; Majewska et al, 2008;Abimosleh et al, 2012;Szczerbińska et al, 2014). Moreover, emus show high adaptive abilities to different climatic conditions.…”
Section: Research Articlementioning
confidence: 99%
“…It will be suggested that increase of crypt cell proliferation protected mucosa (vill) and crypt length [24]. Tazuke et al demonstrated an increase in small intestinal crypt cell proliferation following glutamine administration in a rat model of chemotherapy (cisplatin)-induced mucosal injury [25].…”
Section: Discussionmentioning
confidence: 99%